A Rational Cluster Strategy: Manoeuvring between Market and Government Failures - Evgeniy Kutsenko (Foresight and STI Governance)
Debates on the viability—and the extent of public intervention—that are requisite in the formation and development of clusters are ongoing. It seems, on one hand, that there are few cases of systematic and successful cluster creation from the ground up. On another, clusters shaped without any contribution from government are difficult to find. In this sense, the empirical evidence will not readily provide an answer to the questions, how much intervention is needed and are the existing tools adequate for creating clusters.